Extent of adoption gaps in good management practices (GMPs) of shrimp - Kumaran, M; Alagappan, M; Raja, S; Sarada, C; Vimala, D D; Chandrasekaran, V S; Kalaimani, N (Indian Journal of Fisheries, 2011)
Adoption is a mental process through which an individual eventually make a decision to follow an innovation after carefullyevaluating its relative advantage, compatibility, complexity, visibility and adoptabilityvis-Ã -vis his biophysical and socioeconomicenvironment. An investigation carried out among the shrimp farmers of Andhra Pradesh (AP) and Tamil Nadu(TN) to assess the 'adoption-gap' in Good Management Practices (GMPs) of shrimp culture has found that about 68 and 72%of the GMPs of shrimp farming were adopted by the farmers of AP and TN and an average adoption gap of 32 and 28% wasnoticed in AP and TN respectively. Adoption of aquaculture guidelines like Effluent Treatment System (ETS) needs masseducation, voluntary cooperation and maximum motivation among the farmers. A strong extension support to facilitate theabove is absolutely essential. Further, educational status, occupation, farm size, training, farm experience and social participationof the shrimp farmers aid significantly in minimizing their adoption gap.